Cohesin and CTCF do not assemble TADs in Xenopus sperm and male pronuclei - Jessberger, Gregor; Várnai, Csilla; Stocsits, Roman R.; Tang, Wen; Stary, Georg; Peters, Jan-Michael (Genome Research, 2023)
Paternal genomes are compacted during spermiogenesis and decompacted following fertilization. These processes are fundamental for inheritance but incompletely understood. We analyzed these processes in the frog Xenopus laevis, whose sperm can be assembled into functional pronuclei in egg extracts in vitro. In such extracts, cohesin extrudes DNA into loops, but in vivo cohesin only assembles topologically associating domains (TADs) at the mid-blastula transition (MBT). Why cohesin assembles TADs only at this stage is unknown. We first analyzed genome architecture in frog sperm and compared it to human and mouse. Our results indicate that sperm genome organization is conserved between frogs and humans and occurs without formation of TADs. TADs can be detected in mouse sperm samples, as reported, but these structures might originate from somatic chromatin contaminations. We therefore discuss the possibility that the absence of TADs might be a general feature of vertebrate sperm. To analyze sperm genome remodeling upon fertilization, we reconstituted male pronuclei in Xenopus egg extracts. In pronuclei, chromatin compartmentalization increases, but cohesin does not accumulate at CTCF sites and assemble TADs. However, if pronuclei are formed in the presence of exogenous CTCF, CTCF binds to its consensus sites, and cohesin accumulates at these and forms short-range chromatin loops, which are preferentially anchored at CTCF's N terminus. These results indicate that TADs are only assembled at MBT because before this stage CTCF sites are not occupied and cohesin only forms short-range chromatin loops.
10.1101/gr.277865.123